The Korean Financial System Overcoming the Global Financial Crisis and Addressing Remaining Problems - Tsutsumi, Masahiko (OECD Publishing, 2010)
The intensification of the global financial crisis in late 2008 led to large capital outflows from Korea and turmoil in its capital markets. However, the prompt response by the government and the central bank stabilised Korea's financial sector in early 2009 and recovery followed relatively quickly. In contrast to 1997, financial institutions have overcome the crisis without significant damage. Increased assistance for small and medium-sized enterprises has played a large role in overcoming the crisis, but should be scaled back to avoid supporting non-viable firms and to expand banks' capacity for risk appraisal, leading to a more market-oriented financial system. As a small open economy, Korea also needs to reduce its vulnerability to sudden capital outflows. In addition, it is important to use prudential regulations effectively to limit the risk of mortgage lending, upgrade the corporate governance of financial institutions and develop securitisation by ensuring transparency
Keywords: Economics; Korea, Republic of